Sara Carramiñana, or How to Get Out of the Comfort Zone: Making 3D Animation in Japan - Silvia Carpizo de Diego (Con A de Animación, 2019)
Sara Carramiñana (Calahorra, 1981), has been animating in Japan for more than four years. She hold a Degree in Architecture and a Master's Degree in Animation from Universitat Politècnica de València. Her master degree short film, Death Scissors (2011) won the Ibercaja Animation Award and it was selected at several festivals in Spain and South America. He made her first commissioned animations in Flash at Jam Media, a company from Belfast (Ireland), for the Zig & Zag series (2016-), broadcasted in Ireland and United Kingdom. But the country of the Rising Sun called her and finally she changed the clovers for cherry blossoms, the set dancing for the "bon odori", and the "bodhran" for the "taiko". In Japan she has worked mainly as a CGI animator for movies and series, some of them as popular as Houseki no kuni (Kodansha, Toho, 2017-), which spectacularly combines 3D animation with a 2D animation aspect. Sara tells us her experience in Japan for Con A animación.